The influence of angiopoietin-like protein 3 on macrophages polarization and its effect on the podocyte EMT in diabetic nephropathy - Ma, Yanli; Chen, Yu; Xu, Hong; Du, Ni (Frontiers in Immunology, 2023)
Background Podocyte injury, which involves the podocyte epithelial-mesenchymal transition (EMT) process, is a crucial factor contributing to the progression of diabetic nephropathy (DN) and proteinuria. Our study aimed to examine the protective properties of Angiopoietin-like protein 3 (Angptl3) knockout on podocyte damage and macrophage polarization in DN mice and podocytes treated with HG. Furthermore, we also sought to investigate the underlying molecular mechanism responsible for these effects. Methods DN was induced in B6;129S5 mice through intraperitoneal injection of 40 mg/kg of streptozotocin (STZ). Subsequently, the changes in renal function, podocyte apoptosis, inflammatory factors (tumor necrosis factor-α [TNF-α], interleukin-6 [IL-6], and interleukin-1β [IL-1β]), IL-10, TGF-β1, IL-1Ra, IL-10Ra, and nephrin were evaluated. Moreover, we investigated the mechanism underlying the role of Angptl3 in macrophages polarization, podocyte injury, podocyte EMT. Results Our findings revealed that Angptl3 knockout significantly attenuated STZ or HG-induced renal dysfunction and podocyte EMT. In both in vivo and in vitro studies, Angptl3 knockout led to (1) promote the transformation of M1 type macrophages into M2 type macrophages; (2) amelioration of the reduced expression of nephrin, synaptopodin, and podocin; (3) inhibition of NLRP3 inflammasome activation and release of IL-1β; and (4) regulation of α-SMA expression via the macrophage polarization. (5) After HG treatment, there was an increase in pro-inflammatory factors and foot cell damage. These changes were reversed upon Angptle knockdown. Conclusion Our study suggests that the knockout of Angptl3 alleviates podocyte EMT and podocyte injury by regulating macrophage polarization.